Synthesised magnetic nano-zeolite as a mycotoxins binder to reduce the toxicity of aflatoxins, zearalenone, ochratoxin A, and deoxynivalenol in barley - Karami-Osboo, Rouhollah; Maham, Mehdi; Nasrollahzadeh, Mahmoud (IET nanobiotechnology, 2020)
Agricultural commodities, particularly cereals can be contaminated with mycotoxins during the pre- and post-harvest stage. The main goal of this study was to evaluate the efficacy of magnetic zeolite nanocomposite (MZNC) as an adsorbent for the reduction of mycotoxins in barley flour. The MZNC is synthesised using an eco-friendly and efficient procedure and characterised by zeta potential, field emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The adsorbent amount that affects the adsorption capacity was optimised. Low amounts of the nanocomposite removed >99% of aflatoxins, 50% of ochratoxin A, 22% of zearalenone, and 1.8% of the deoxynivalenol from the contaminated sample and adsorption by MZNC was better than the natural zeolite; this phenomenon is related to the wide surface of nanocomposites. Results provide new insights into possible future research that could overcome the challenges of using nanotechnology to eliminate mycotoxins from agricultural products. It can be hoped that the presence of cheap and eco-friendly mycotoxin binders such as the MZNC that is synthesised and utilised in this research will help to produce secure food and feed products.